Hybrid of Eddy Current Probe Based on Permanent Magnet and GMR Sensor - Faraj, Moneer A.; Fahmi, Samsuri; Abdalla, Ahmed N. (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
The eddy current testing (ECT) is used to inspect a material to determine its properties without destroying its utility. The applications include detection of flaws in aircrafts, pipeline, etc. An ECT is a weak sensitivity to a subsurface defect. Applications of giant magnetic sensors (GMR) are increasingly applied to the measurement of weak magnetic fields related to the currents they cause. In this paper, GMR sensor with magnet bar (permanent) is utilized. The proposed probe system is utilized to study the impact of the width and depth defect on the signal of eddy current testing. The maximum depth of flaw in a mild steel can be revealed by using this probe. The graph of the difference between the peak amplitude and the penetration depth of each slot of a different width of the two bands of mild steel shows the increase of the signal for each slot and flat above 3mm. The experimental result proves the inability of a PMGMR probe to detect a defect at a depth of 3mm on a surface defect.